Review on Different Biomass Based Microbial Desalination Cell Catalyzed by Bacteria and Yeast - Ghazal, Diana; Shahin, Aya (My University, 2020)
Abstract Existing desalination technologies require high amounts of power and electricity that accordingly produces high amounts of greenhouse gasses. Therefore, it is required to introduce a new technology that can produce electricity from organic sources as well as desalinate water at the same time. Microbial desalination cell (MDC) is the new technology that is composed of three chambers: anode, middle desalination chamber and cathode. The middle desalination chamber is isolated by anion exchange membrane (AEM) and a cation exchange membrane (CEM). The electron was produced in the anode by bacteria and transferred via an external circuit to the cathode thus producing current. When current is produced at the anode, ionic species in the desalination chamber were transferred into the two electrode chambers, so desalinating the water. Different parameters affect the MDC’s efficiency. Hence it is the aim of this project to test the effect of these parameters on the MDC efficiency. This includes: the kind and amount of biomass used, water salinity, and the optimum volume of desalination volume. The efficiency of MDC cell is observed through the output power in addition to the desalination rate. Experimental work with the MDC was carried out using Fungi and bacteria microorganisms. When MDC was operated using fungi with glucose as the substrate, the maximum open circuit potential of cell operated fungi abstracted from mango was 800 mV and achieved 1.4% salt removal, while fungi abstracted from banana was more stable and was 450mV. MDC operated using bacteria and acetate 1.6 g/L at ambient temperature to achieve a peak of open circuit potential at 500 mV and 20% salt removal. While the experiment was done using a 40% desalination chamber achieve a peak of closed-circuit potential, current and power values using 200 Ω as external resistance at 770mV, 3.8 mA/m2, and 5.8 W/m2, respectively. Also, the salinity of water for this experiment was decreased and the percentage of salt removal was found 65.4%. Effect of temperature was tested in one experiment and found that the maximum open circuit potential was of 954 mV at 50˚C.